2015
DOI: 10.1007/s12603-015-0496-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum polyunsaturated fatty acid composition and serum high-sensitivity C-reactive protein levels in healthy Japanese residents: The Kobe study

Abstract: Patients with AD that received DBS of the nucleus basalis of Meynert demonstrated a mainly stable nutritional status within a 1-year period. Whether DBS is causative regarding these observations must be investigated in additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…We found a strong negative correlation between serum n-6 and n-3 PUFA and the markers of inflammation (ESR, CRP). The negative relationship between serum n-3 PUFA compositions and correlating CRP level in adults has been reported by other authors [ 48 , 49 ]. Pirschon et al [ 45 ] in a large population found an inverse relationship between an intake of n-3 PUFA and CRP levels, as well as a strong inverse association between high n-6 intake and soluble tumor necrosis factor receptors 1 and 2.…”
Section: Discussionsupporting
confidence: 79%
“…We found a strong negative correlation between serum n-6 and n-3 PUFA and the markers of inflammation (ESR, CRP). The negative relationship between serum n-3 PUFA compositions and correlating CRP level in adults has been reported by other authors [ 48 , 49 ]. Pirschon et al [ 45 ] in a large population found an inverse relationship between an intake of n-3 PUFA and CRP levels, as well as a strong inverse association between high n-6 intake and soluble tumor necrosis factor receptors 1 and 2.…”
Section: Discussionsupporting
confidence: 79%
“…Data collection for other characteristics at the follow-up survey was conducted in accordance with the baseline survey of the KOBE study [4][5][6][7]10]. Similar questionnaires were modified for the CI patients.…”
Section: Data Collectionmentioning
confidence: 99%
“…Subjects with a low intake of omega-3 fatty acids had higher levels of CRP and vice versa [29]. A similar study by Kubota et al (2015) comparing serum levels of FUFA (polyunsaturated fatty acid) and hs-CRP levels in a healthy Japanese population found that serum omega-3 and serum omega-6 levels had an inverse relationship to serum hs-CRP levels [30]. Different research results were reported by Flock et al (2014), who found that EPA and DHA supplementation with varying doses of 300, 600, 900, and 1800 mg/d for five mo in healthy adults had no effect on levels of the inflammatory biomarker CRP, TNF-α and IL-6 [31].…”
Section: Hs-crp Levelsmentioning
confidence: 91%